A qualitative study on classroom management and classroom discipline problems, reasons and solutions: the case of a literature class / Nurhayati Ghazali - Ghazali, Nurhayati (2010)
The purpose of this study was to investigate classroom management and discipline problems that Literature teachers have faced, and to reveal the underlying reasons and possible solutions of these problems by considering the views of teachers and administrators. This study was designed as a qualitative study. Subjects of this study consisted of 5 school administrators and 5 teachers. Two different, but parallel, semi-structured interview schedules were used for data collection. Data was analyzed through the use of the content analysis method. As a result of this analysis, the problems associated with classroom management were grouped under the following themes; lack of motivation, rule and routines breaking, boring literature texts/materials, ineffective time management, classroom environment, language barrier and lack of classroom interaction. On the other side, participants relate these problems with the following reasons; nature and status of the subject in the curriculum, classroom environment, crowded classroom and boring literature texts/materials, lack of rules, teachers’ inefficiency in classroom management and students’ attitudes. Finally, the following solutions were suggested to overcome disciplines and classroom management problems; increasing teachers’ pedagogical and subject area knowledge, re-framing the nature of literature course/subject in the curriculum, using a reward system that facilitates motivation, establishing classroom rules, giving punishment, ignoring, investigating the reasons of the problem, encouraging students’ creativity to incorporate the texts into their daily lives to make it interesting, using the influence of the English Language Society to promote Literature to the students in the school and collecting feedback from students about the subject and adhering to their needs.